2023
DOI: 10.1186/s12944-022-01770-3
|View full text |Cite
|
Sign up to set email alerts
|

Astragalus polysaccharide prevents heart failure-induced cachexia by alleviating excessive adipose expenditure in white and brown adipose tissue

Abstract: Background Astragalus polysaccharide (APS) is a key active ingredient isolated from Astragalus membranaceus that has been reported to be a potential treatment for obesity and diabetes by regulating lipid metabolism and adipogenesis, alleviating inflammation, and improving insulin resistance. However, whether APS regulates lipid metabolism in the context of cachexia remains unclear. Therefore, this study analysed the effects of APS on lipid metabolism and adipose expenditure in a heart failure (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(16 citation statements)
references
References 60 publications
2
14
0
Order By: Relevance
“…Additionally, in our study, we found beiging markers, including Ucp-1, Cd137, Tbx-1 and Zic-1, indicating increased beiging of WAT in HF-induced cachexia by MCT injection. This was consistent with our previous study using a salt-sensitive hypertension-induced cardiac cachexia rat model [20]. Moreover, our study showed, for the rst time, that disrupted circadian rhythm aggravates beiging of WAT in HF-induced cachexia.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Additionally, in our study, we found beiging markers, including Ucp-1, Cd137, Tbx-1 and Zic-1, indicating increased beiging of WAT in HF-induced cachexia by MCT injection. This was consistent with our previous study using a salt-sensitive hypertension-induced cardiac cachexia rat model [20]. Moreover, our study showed, for the rst time, that disrupted circadian rhythm aggravates beiging of WAT in HF-induced cachexia.…”
Section: Discussionsupporting
confidence: 93%
“…In the lipolysis process, TGs stored within lipid droplets are hydrolysed into FFAs and released as fuel in peripheral tissues according to metabolic demand. In the hypermetabolism state of cachexia, excessive TGs are hydrolysed, causing not only adipocyte atrophy but also increased FFA ectopic deposition in peripheral tissue [20]. As described previously, fatty liver and elevated blood levels of FFAs were found in cachexia caused by cancer and severe burn injury [36].…”
Section: Discussionmentioning
confidence: 84%
See 1 more Smart Citation
“…In addition, in ovo injection of 2 mg APS per egg significantly enhanced VH and the ratio of VH/CD and improved intestinal morphology and development of chicks, resulting in marked increase on average daily feed intake (ADFI), body weight (BW), and FCR of layer chicks ( 127 ). Interestingly, recent studies revealed that APS could regulate lipid metabolism and adipogenesis ( 128 ). A previous study reported that in ovo injection of 4.5 mg APS enhanced carcass percentage, reduced abdominal fat, as well as reduced educed triglycerides, total cholesterol, low-density lipoproteins, and very low-density lipoproteins in the plasma of broilers ( 129 ).…”
Section: Effects Of Aps On Animal Productionmentioning
confidence: 99%
“…reported that Astragalus polysaccharide, a key active ingredient isolated from HQ, prevents heart failure‐induced cachexia by alleviating excessive adipose expenditure in white and brown adipose tissue. 14 HQ injection, which is a formulation of an extract of HQ, is a most commonly used type of proprietary Chinese medicine for the clinical operation of treating chronic heart failure. There were 62 randomized controlled trials (RCTs) and quasi‐RCTs evaluated.…”
Section: Introductionmentioning
confidence: 99%